Developing a Problem-Based Learning Model Integrated with Socio-Scientific Issues to Enhance Pre-Service Primary Teachers’ Argumentation Skills: A Need Analysis - Issaura Sherly Pamela; M. Rusdi; Asrial Asrial; Muhammad Haris Effendi Hasibuan (Yayasan Adra Karima Hubbi, 2026)
Background. Argumentation skills are essential competencies in 21st-century science education, particularly for pre-service primary school teachers. However, students’ scientific argumentation skills remain relatively low, especially in constructing claims, using evidence, and providing scientific reasoning. Innovative learning models that integrate contextual and argumentative learning experiences are therefore needed in higher education. Purpose. This study analyzed the need for developing a Problem-Based Learning (PBL) model integrated with Socio-Scientific Issues (SSI) to enhance the argumentation skills of pre-service primary school teachers. Method. A descriptive survey design was employed involving 35 pre-service primary school teachers from Universitas Jambi and 5 lecturers teaching science education courses at several Indonesian universities. Data were collected using open-ended and close-ended questionnaires and analyzed through descriptive statistical analysis and qualitative categorization techniques. Results. Students perceived the current condition of science learning at a moderate level (M = 3.40), while lecturers reported a higher perception (M = 4.35), indicating that although science learning has provided discussion opportunities, it has not yet systematically supported students’ scientific argumentation skills. The integration of PBL and SSI in current instructional practices received high ratings from both groups (students: M = 4.18; lecturers: M = 4.48). Notably, the strongest agreement was found regarding the need to develop a PBL-SSI integrated model (students: M = 4.61; lecturers: M = 4.82), confirming a strong demand for a structured learning model to better support scientific argumentation among pre-service teachers. Conclusion. Developing a PBL-SSI integrated learning model is necessary to support the improvement of argumentation skills among pre-service primary school teachers. These findings serve as a foundation for designing innovative science learning models that promote scientific argumentation, critical thinking, and contextual learning in Indonesian higher education.